Intercropping system of tropical leguminous species and Eucalyptus camaldulensis , inoculated with rhizobia and/or mycorrhizal fungi in semiarid Brazil - Pagano, Marcela C. (2008)
For the purpose of reforestation and wood supply the leguminous tree Anadenanthera peregrina, a native species, was intercropped with Eucalyptus camaldulensis in a degraded semiarid area of Brazil. Single and mixed stands of these species were inoculated with Rhizobium and/or arbuscular mycorrhizal fungi (AMF). The growth of all species in mixed stands did not differ from those cultivated in monoculture and land equivalent ratio (LER) exceeded unity in intercropped plots. Inoculated plants showed greater height and diameter growth and dry matter and nutrient concentration in plants of A. peregrina was higher in inoculated single plots. The distribution, composition and density of AMF species was related to the rhizosphere effect of plant species. The intercropped model where all the plants were inoculated achieved soil AMF diversity patterns similar to those of the preserved area and showed also higher soil organic matter, nutrient content as well as a reduction in soil macroporosity. This model of intercropping may be considered as an efficient system for reforestation under semiarid conditions.